A Teaching Model in Physical Education Based on the Social Cognitive Perspective of Self-Regulated Learning - Kolovelonis, Αθανάσιος; Goudas, Μάριος (Inquiries in Physical Education and Sport, 2014)
The aim of this study was to present an approach for teaching motor and sports skills in physical educa-tion. This approach was based on social cognitive perspective of self-regulated learning and empirical re-search that support it. According to this approach, learning of motor and sports skills in physical education begins with the provision of brief oral instructions followed by practice with social feedback. Then, students practice autonomously the skill setting goals and self-monitoring their performance. Finally, at the self-regulated level, students practice to maximize their performance and to adopt the skill in changing condi-tions. Physical educators can incorporate this teaching model into their teaching repertoires to teach motor and sport skill in physical education.